Prognostic value of neutrophil-to-lymphocyte ratio in cirrhotic patients with acute-on-chronic liver failure - Chiriac, Stefan; Stanciu, Carol; Singeap, Ana Maria; Sfarti, Catalin Victor; Cuciureanu, Tudor; Trifan, Anca (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Patients with cirrhosis hospitalized in the intensive care unit (ICU) have a high risk for acute-on-chronic liver failure (ACLF) and short-term mortality. A major factor in the pathogenesis of ACLF is systemic inflammation, the assessment of which includes the use of surrogate markers, such as neutrophil-to-lymphocyte ratio (NLR). This study aimed to assess the accuracy of NLR in predicting the outcome of patients with cirrhosis and ACLF hospitalized in the ICU.Materials and Methods: This was a retrospective observational study on patients with cirrhosis with acute decompensation hospitalized in the ICU of a Romanian tertiary care center. ACLF was defined according to the CANONIC criteria, and NLR was calculated by dividing the absolute neutrophil count by the absolute lymphocyte count.Results: A total of 70 patients were included, of whom 70% were men with a mean age of 62±6.2 years. ACLF was diagnosed in 58 (82.9%) patients who presented with higher in-hospital mortality rates than patients without ACLF (84.5% vs. 33.3%, p=0.001). The mean NLR value was 11.7±9.5, higher in non-survivors than in survivors (12.6±9.8 vs. 8.6±7.8, p=0.170). NLR had a poor accuracy in predicting the outcome in patients without ACLF (area under the curve [AUC]=0.611) but a better accuracy in patients with ACLF (AUC=0.776). Patients with cirrhosis and a high NLR had higher levels of bilirubin; higher Child-Turcotte-Pugh score; and higher incidence of ascites, coagulation, and circulatory failure, presenting a poor outcome. Receiver operating characteristic analysis showed a good accuracy for predicting mortality for the Child-Turcotte-Pugh score (AUC= 0.864) and NLR (AUC=0.732).Conclusion: NLR is a promising and cost-effective method for the prediction of a poor outcome in critically ill patients with cirrhosis hospitalized in the ICU and shows greater accuracy in those with ACLF.